(untitled) (Research, Society and Development, 2023)
Attention Deficit Hyperactivity Disorder (ADHD) is considered a condition of human neurodevelopment that is characterized by a triad of symptoms involving inattention, hyperactivity and impulsivity at an exacerbated and dysfunctional level for age, which affects between 3% to 8% of children and teenagers. The aim of this study was to understand the importance of family monitoring during the development and treatment of children with ADHD. This was an integrative review study with a qualitative approach. Data collection took place between January and March 2023 using Boolean descriptors and operators “Attention Deficit Disorder with Hyperactivity” AND “Family Relationship” AND “Child Health” AND “Mental Health” indexed in the Virtual Library portal in Health (VHL) – LILACS and MEDLANE, articles published in English and Portuguese from 2017 to 2023. The selected sample consists of 12 articles, according to inclusion and exclusion criteria. According to the analyzes of the selected studies, some difficulties in the family relationship in the daily life of children with ADHD were highlighted. Thus, these studies showed that the family interactions of parents and children diagnosed with ADHD are characterized by more conflicts, coercion and stress. In addition, it is necessary to develop research projects to improve the quality of life and develop possibilities for healthier and qualitatively more positive interpersonal, family and social relationships for this child with ADHD.